Exploring the nexus between health status, technical efficiency, and welfare of small-scale cereal farmers in Tanzania: A stochastic frontier analysis - Kitole, Felician A; Tibamanya, Felister Y; Sesabo, Jennifer K (Journal of Agriculture and Food Research, 2024)
A research article submitted to the Journal of Agriculture and Food Research, Vol.15 of 2024.